Construction of heat stress regulation networks based on Illumina and SMRT sequencing data in potato - Shang, Lina; Zhou, Yonghong; Wen, Shiqi; Wang, Ke; Li, Yang; Zhang, Meihua; Jian, Hongju; Lyu, Dianqiu (Frontiers in Plant Science, 2023)
Potato (Solanum tuberosum L.) is one of the most important tuber food crops in the world, however, the cultivated potatoes are susceptible to high temperature, by which potato production is adversely affected. Understanding the coping mechanism of potato to heat stress is essential to secure yield and expand adaptability under environmental conditions with rising temperature. However, the lack of heat-related information has significantly limited the identification and application of core genes. To gain deeper insights into heat tolerance genes, next-generation sequencing (NGS) and single molecular real-time sequencing (SMRT) were used to learn the transcriptional response of potato to heat stress and 13,159 differentially expressed genes (DEGs) were identified in this study. All DEGs were grouped into 12 clusters using the K-means clustering algorithm. Gene ontology (GO) enrichment analysis revealed that they were involved in temperature signaling, phytohormone and protein modification. Among 2 / 28 them, there were 950 differentially expressed transcription factors (DETFs). According to the network analysis of DETFs at the 6 th hour under heat stress, we found some genes that were previously reported to be associated with photoperiodic tuberization, StCO (CONSTANS), tuber formation, StBEL11 (BEL1-LIKE 11) and earliness in potato, StCDF1 (CYCLING DOF FACTOR 1) responding to temperature. Further, we verified the relative expression levels using qRT-PCR, and the results were consistent with the inferences from transcriptomes. In addition, there were 22,125 alternative splicing (AS) events and 2,048 long non-coding RNAs (lncRNAs). The database and network established in this study will extend our understanding of potato response to heat stress.It ultimately provided valuable resources for molecular analysis of heat stress response in potato and cultivation of potato varieties with heat tolerance.